Negative Correlation Between Social Media Intensity and Emotional Intelligence: Korelasi Negatif Antara Intensitas Penggunaan Media Sosial dan Kecerdasan Emosional - Ardiyanti; Widyastuti (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The rapid growth of internet penetration in Indonesia has positioned social media as an integral part of daily life, particularly among vocational high school students, raising concerns regarding emotional development in the digital era. Specific Background: Emotional intelligence, conceptualized through self-awareness, emotion regulation, self-motivation, empathy, and relationship management, is considered essential for students’ character formation, while intensity of social media use is reflected in frequency, duration, attention, and emotional engagement. Knowledge Gap: Although prior studies report associations between social media use and emotional intelligence, empirical evidence focusing on students at SMK Plus NU Sidoarjo remains limited. Aims: This study aimed to determine the relationship between intensity of social media use and emotional intelligence among students of SMK Plus NU Sidoarjo. Results: Using a quantitative correlational design with simple random sampling, data from 158 students were analyzed through Pearson product moment correlation. Findings revealed a significant negative correlation (r = -0.435; p = 0.000 < 0.05), indicating that higher intensity of social media use corresponds with lower emotional intelligence. Most students demonstrated moderate levels of social media intensity (69.6%) and emotional intelligence (63.3%). Novelty: This study provides institution-specific empirical data integrating validated measures of social media intensity and emotional intelligence within a vocational school context. Implications: The findings underscore the need for guided and balanced social media practices to support emotional regulation and social competence among vocational high school students. Highlights: Statistical Testing Demonstrated a Significant Inverse Association Between the Two Measured Variables (R = -0.435; P < 0.05). The Majority of Participants Were Categorized at a Moderate Level for Both Measured Constructs. Linear Model Assumptions Were Satisfied Based on Normality and Linearity Testing Prior to Hypothesis Examination. Keywords: Social Media Intensity, Emotional Intelligence, Vocational High School Students, Pearson Correlation, Quantitative Correlational Study